Draft genome sequence of the immunobiotic strain Lactobacillus jensenii TL2937 - Villena, Julio Cesar (2017)
The genome of the immunomodulatory strain Lactobacillus jensenii TL2937 is described here. The draft genome has a total length of 1,678,416 bp, a G+C content of 34.3%, and 1,470 predicted protein-coding sequences. The genome information will be useful for gaining insight into the immunomodulatory properties of the TL2937 strain in the porcine host.